The Role of GABA in Anxiety Disorders - Jest Phia, Wong (Journal of Science & Technology, 2024)
Gamma-aminobutyric acid (GABA) is the primary inhibitory transmitter in the central nervous system (CNS). One third of all CNS neurons are thought to be GABAergic. GABA is present in relatively high concen trations in the spinal cord and in all regions of the brain but does not exist in neurons outside the CNS.The inhibitory action of GABA on neuronal activity in the CNS counterbalances the action of the excitatory neurotransmitter glutamate (Figure 1). The mutual homeo- stasis between glutamate and GABA works to modulate neuronal excitability and CNS arousal. This balance pre- vents excessive levels of neuronal hyperexcitability, which are known to occur in seizure disorders and pathologic anxiety and angiogenesis.
Keywords: GABA; Anxiety Disorders